Investigating Different DNA Methylation Patterns at the Resolution of Methylation Haplotypes - Peng, Xiaoqing; Li, Yiming; Kong, Xiangyan; Zhu, Xiaoshu; Ding, Xiaojun (Frontiers in Genetics, 2021)
Different DNA methylation patterns presented on different tissues or cell types are considered as one of the main reasons accounting for the tissue-specific gene expressions. In recent years, many methods have been proposed to identify differentially methylated regions (DMRs) based on the mixture of methylation signals from homologous chromosomes. To investigate the possible influence of homologous chromosomes on methylation analysis, a method, named MHap, is proposed to construct methylation haplotypes for homologous chromosomes in CpG dense regions. Then, a simple method, MHap_DMR, is developed to identify DMRs based on methylation haplotypes. Through comparing the methylation consistency between homologous chromosomes in different cell types, we found that majority of paired methylation haplotypes derived from homologous chromosomes are consistent, while a lower methylation consistency was observed in the breast cancer sample. We also observed that the hypomethylation consistency of differentiated cells is higher than that of the corresponding undifferentiated stem cells. The methylation haplotype modes of DMRs identified by MHap_DMR can help to investigate the DNA methylation changing directions of homologous chromosomes in cell differentiation and cancerization. The code is available at https://github.com/xqpeng/MHap_DMR.